Ontologi Dan Epistemologi Makna Dalam Bahasa Arab: Perspektif Filsafat Bahasa - Qur’ani Izzati Rahmah Muhammad (Jurnal Pendidikan Indonesia, 2025)
This study explores the concepts of ontology and epistemology of meaning in the Arabic language through the lens of the philosophy of language, highlighting the relationship between the existence of meaning, the process of its formation, and how it is understood. The primary issue addressed is how meaning in Arabic is influenced by the ontological and epistemological structures inherent in the language, particularly in relation to its use across various social, cultural, and historical contexts. The study aims to identify and analyze the philosophical foundations that shape meaning in Arabic and to examine how meaning is understood and represented through linguistic symbols. The method used in this research is the literature review method. The findings indicate that meaning in Arabic is characterized by complexity, involving the interaction between symbols, concepts, and reality, and is significantly influenced by cultural and social factors. Furthermore, meaning in Arabic exhibits a dynamic dimension, continually evolving with changes in its contextual usage. The study concludes by emphasizing the importance of understanding the ontology and epistemology of meaning in Arabic to provide a deeper insight into the relationship between language, thought, and reality, which is not only relevant in linguistic studies but also in the fields of philosophy, literature, and cultural studies.